Shift work, long working hours, and later risk of dementia: A long-term follow-up of the Copenhagen Male Study - Kirsten Nabe-Nielsen; Anne Helene Garde; Kazi Ishtiak-Ahmed; Finn Gyntelberg; Erik Lykke Mortensen; Thien Kieu Thi Phung; Naja Hulvej Rod; Gunhild Waldemar; Rudi GJ Westendorp; Åse Marie Hansen (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The aim of this study was to investigate the effect of shift work and long working hours in midlife on the risk of dementia in old age. METHODS: The present study comprised 4766 participants from the Copenhagen Male Study. We used information on shift work (collected in 1970-1971 and 1985-1986), long working hours defined as >45 hours per week (collected in 1970-1971), socioeconomic status, sleep, stress, and cardiovascular risk factors. Information about dementia diagnoses was obtained from registers. Participants were followed until 2014 (mean length of follow-up was 17.8 years). We employed Poisson regression for the survival analyses and estimated incidence rate ratios (IRR) and their 95% confidence intervals (CI). RESULTS: We found no statistically significant association between shift work (IRR 0.86, 95% CI 0.70-1.05) or long working hours (IRR 0.97, 95% CI 0.79-1.19) and dementia. Adjustment for potential confounders and mediators did not change the estimates. Working shifts at both time points of exposure assessment was not associated with a higher incidence of dementia compared with non-shift workers at both time points (IRR 0.99, 95% CI 0.69-1.42). The lowest incidence of dementia was observed among participants who reported shift work at one time point (only in 1985-1986: IRR 0.44, 95% CI 0.16-1.23 and only in 1970-1971: IRR 0.58, 95% CI 0.31-1.11). CONCLUSION: We did not find positive evidence of an association between shift work or long working hours and the incidence of dementia, but the negative findings may reflect the crude assessment of shift work and long working hours, which is a major limitation of the present study.